Temporal analysis of doxorubicin-induced cardiac toxicity and hypertrophy - Yu-Te Lin; Yi-Ju Lee; Wen-Wei Tseng; Zih-Hua Chen; Huai-Ching Hsieh; Ko-Hong Lin; Jin-Yu Su; An-Chi Wei (npj Systems Biology and Applications)
Abstract Doxorubicin (DOX), although effective in treating cancer, has significant cardiac side effects, which limit its clinical utility. In this study, we collected time-course transcriptomics and metabolomics data from the human cardiomyocyte cell line AC16, which we analyzed along with curated public transcriptomics data on DOX-induced toxicity. We developed a multiomics analysis workflow and a computational toolbox, pipeGEM, to integrate RNA-seq data with metabolic models, enabling the simulation of DOX-induced metabolic perturbations at a sample-specific level. Our results revealed that DOX affected mitochondrial damage and mitochondria-to-nucleus retrograde signaling, potentially contributing to the observed cellular enlargement, senescence and metabolic shift. Cardiac cells that survived DOX treatment presented elevated glycolysis, increased pentose phosphate pathway activity, an altered TCA cycle, and modified glutathione and fatty acid metabolism. These findings provide a comprehensive understanding of DOX-induced toxicity and its implications for cardiac hypertrophy, suggesting potential strategies to mitigate side effects while retaining the anticancer efficacy of DOX.